Global education and training in geriatrics: mapping transnational initiatives and their complementarities - Romero-Ortuno, Roman (My University, 2026)
Purpose: To map and characterise major transnational initiatives in geriatrics education and training, and explore complementarities as a basis for a more integrated and equitable global framework. Methods: A mapping exercise and expert consultation were undertaken by the European Geriatric Medicine Society (EuGMS) Special Interest Group on Education and Training between January and October 2025, including a meeting of international experts during the Twenty-First EuGMS Congress in Reykjavík. Eligible initiatives operated across national borders with an explicit mandate in education and training related to geriatrics and were not confined to a specific topic or subspecialty. Each initiative was profiled by scope, target audience, and contributions, and classified within a three-tier framework: (1) foundational capacity-building, (2) professional and interprofessional development, and (3) leadership and specialist advancement. Results: Seventeen initiatives were identified. Tier 1 included the International Federation on Ageing (IFA), International Institute on Ageing, United Nations–Malta (INIA), PAHO’s ACAPEM (Basic), ASEAN’s Centre for Active Ageing and Innovation (ASEAN–ACAI), IAGG’s e-Training in Gerontology and Geriatrics (e-TRIGGER) programmes, WHO’s Integrated Care for Older People (WHO ICOPE approach), and AfriAGE. Tier 2 included the IAGG, EuGMS, EICA, PROGRAMMING CA2112, Victorian Geriatric Medicine Training Programme (VGMTP), and ACAPEM (Intermediate); and Tier 3 was represented by leadership academies (EAMA, ALMA, MEAMA/MENAAA, and AAMA), and UEMS–GMS. Conclusion: Collectively, these programmes form a considerably disjointed but potentially complementary global ecosystem for geriatrics education. Greater mutual awareness and alignment, anchored in equity and interprofessional inclusion, could enhance efficiency and sustainability in developing the global geriatrics workforce.
PUBLISHED
Keywords: Geriatrics education; Education; Medical; Continuing; Health workforce; International cooperation; Capacity building; Global health; Ageing; Digital Engagement; Inclusive Society; International Development; International Integration; Smart & Sustainable Planet; Ageing, Older People and Healthcare; Education and training; INTERNATIONALIZATION; Age-related disability; Chronic Health Condition; Accessibility; Education; Globalization; Third age/ageing